Some Aspects of the Experience to Have Exams in Ukrainian Schools in the Second Half of the 19th Century and the Early 20th - Olena Feshchenko (Pedagogical Discourse, 2013)
In this article the author reveals some aspects of the experience of the final exams as a form of control over the level of students’ knowledge  in different types of schools in Ukraine in the second half of the XIX century and early twentieth century. The author highlights the historical conditions in where certain organizational forms and methods of teaching and education of students, the introduction of  control types over their educational achievements were appeared. It is pointed out in historical sources, official legislative documents, including «Provisional rules of Education» (1803 ), «Charters of schools and gymnasiums (1828, 1864, 1871 years), The position of the women's high schools and gymnasia of the Ministry of Education» (1870), and in magazines «Russian School», «Journal of the Ministry of Education», «Questions of history», «Pedagogy» and others.  Nikolai Korf – a methodologistst, an educational figure made a great contribution to start examinations in Ukrainian schools.